Progressive Production Technology of Integral Car Body Shell from Aluminium Alloys (Current Problems in Rail Vehicles, 2021)
Efforts to increase the productivity of the production of integral car body shell from aluminium alloys and to reduce the overall weight of the vehicle lead to the intensive search for progressive production technologies. These include friction stir welding and composite panels. In friction welding, there is less thermal influence at the weld site and thus less deformation after welding than in the currently most commonly used electric arc welding. The advantages of this technology are reflected in both thin- and thick-walled profiles or sheets. Škoda Transportation currently uses this technology in the production of car body shell for singleanddouble-deck vehicles. Today, composite panels are used not only as visible panels of external or internal cladding, but also as load-bearing parts of a car body shell. Examples of applications are structural partitions or floors of double-decker vehicles. The panels consist of a core of aluminium honeycomb, peripheral profiles and a coating of aluminium sheet on both sides. All parts of the panel are glued to each other and can be riveted, screwed or even welded to the rest of the rough construction.
Keywords: FSW; svařování; čelník; composite panels; podlaha